2019
DOI: 10.2147/copd.s178040
|View full text |Cite
|
Sign up to set email alerts
|

<p>COPD: misuse of inhaler devices in clinical practice</p>

Abstract: Background and objectives: Inhalers mishandling remain an important clinical issue worldwide. The aim of this study was to evaluate inhalation technique in stable COPD out-patients. The variables under study were type of inhaler device (ID), patients’ preference for an inhaler, number of IDs used by each patient, beliefs about inhaler medication and some demographic, clinical and functional patients' characteristics. We aim to assess how they are related to inhalation technique. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
60
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 27 publications
6
60
2
2
Order By: Relevance
“…Inhaler misuse is reportedly related to the device type (pMDI), female sex, lower education level, and lower socioeconomic status [ 21 , 22 ]. It is generally accepted that pMDI is more error prone than DPI, but studies are inconsistent in the findings of comparisons of DPIs, making it difficult to determine that a particular device shows fewer errors [ 22 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhaler misuse is reportedly related to the device type (pMDI), female sex, lower education level, and lower socioeconomic status [ 21 , 22 ]. It is generally accepted that pMDI is more error prone than DPI, but studies are inconsistent in the findings of comparisons of DPIs, making it difficult to determine that a particular device shows fewer errors [ 22 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Khurana et al suggested that the ability to handle and use the device is one of the three main characteristics that determine drug deposition into the lungs, alongside technical characteristics of the device and the drug formulation [24]. Ineffective inhaler technique, potentially due to poor training when prescribed [25], can influence patient adherence and the perception of device performance, often based on the patient's beliefs about inhaler medication [26].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve an optimal therapeutic effect, patients must perform a correct inhalation technique. The use of an incorrect inhalation technique is one of the most frequent causes of therapeutic failure when inhalation devices (IDs) are used [2]. Carrying out inhalation correctly mainly depends on the patient completing all the steps described for performing this inhalation for each ID as well as avoiding critical errors [3].…”
Section: Introductionmentioning
confidence: 99%